Cytomegalovirus infection in solid organ transplant recipients. (September 2014) - Lumbreras, C.; Manuel, O.; Len, O.; ten Berge, I. J. M.; Sgarabotto, D.; Hirsch, H. H.; ,
Abstract: Cytomegalovirus (CMV) is the most frequent infectious complication following solid organ transplantation (SOT). The virus, is responsible for both direct (viral syndrome, hepatitis, pneumonitis, colitis, etc.) and indirect effects (rejection, infections by other microorganisms and graft dysfunction). In this evidence‐based guideline we deal with the most important aspects of CMV infection in SOT recipients, including pre‐ and post‐transplant diagnosis assessment and risk factors, with special emphasis on the prevention and treatment of this viral infection. Overall, adequate management of CMV infection is a critical aspect of transplant patient care.